Constitucionality of the child support legal process without audience - Huanca Luque, Adolfo (2020)
This study looks at cases of belated justice in child support. This problem was understood by all the parties and by the judges. Consequently, the Child Support Legal Process was reformed: it was through the modification of the Unique Legal Process that now the possibility of the Child Support Legal Process without audience exists. This changed the flexibility of the Legal Process and they are according to the constitutional law. This change facilitated the solution of the cases in 16 to 19 days.